S100 Calcium-Binding Proteins and Ion Channels - Anton eHermann; Rosario eDonato; Thomas M. Weiger; Walter J. Chazin (Frontiers Media S.A., 2012)
S100 Ca2+-binding proteins have been associated with a multitude of intracellular Ca2+-mediated functions including regulation of the cell cycle, cell differentiation, cell motility and apoptosis, modulation of membrane-cytoskeletal interactions, transduction of intracellular Ca2+ signals, and in mediating learning and memory. S100 proteins are fine tuned to read the intracellular free Ca2+ concentration, modulate protein phosphorylation, and compete with calmodulin for binding sites, which makes them strong candidates to modulate neuronal electrical behaviour. Certain S100s are secreted from cells and are found in extracellular fluids where they exert unique extracellular functions. In addition to their neurotrophic activity, certain S100 proteins modulate neuronal electrical discharge activity and appear to act on ion channels. The first reports regarding these effects suggested S100-mediated alterations in Ca2+ fluxes, K+ currents and neuronal discharge activity. Recent reports revealed direct and indirect interactions with Ca2+, K+, Cl- and ligand activated channels. This review focuses on studies of the physical and functional interactions of S100 proteins and ion channels.